Ideas for Enhancing Security of (Sports)Events (Academic Journal of Internal Affairs, 2020)
One of the guarantee elements for the safe conduct of (sports) events is the safeguarding of events, which is one of the priority tasks of domestic and international sports life. At the same time, maintaining order and security is a rather complex, multiplayer task nowadays, in which the state has lost its monopoly position due to the emergence of the private security sector. The guarantee for safeguarding of (sports) events is the task of the trained specialists, for which it is essential to create an appropriate level and quality of education, and training background for those employed in the sector. The study shows that due to the lack of institutional professional training in Hungary, the qualification of professionals with adequate safety knowledge in sports facilities is far below the desired level. The article draws attention to the fact that the low level of professionality in event safeguarding is a significant risk factor for sports and other events, especially at a time when the sector under study is has a high priority for future development.
Keywords: security; event; sports event; sports security training